Perlindungan Hukum Bagi Pengusaha Clothing Terhadap Peniruan Merek Oleh Pihak Lain (Studi Kasus di Nimco Mega Store Surakarta) - Ristiyani, Etik, Inayah, S.H., M.H (2017)
Legal protection of the brand in the trade of goods and services are absolutely necessary to prevent and avoid practices that are dishonest, such as imitation brand and obtain legal certainty. The provisions in the Act No. 15 of 2001 on Marks explains that the rights to the brands acquired when the brand is registered in the General Register of Marks. In case of violation of the trademark, the trademark owner has the authority to take legal actions in accordance regulated in Law No. 15 of 2001 on Marks. Another attempt can be made through arbitration or alternative dispute resolution that resulted in a decision in the form of cessation of actions relating to the use of the mark being imitated.